2006
DOI: 10.3748/wjg.v12.i15.2398
|View full text |Cite
|
Sign up to set email alerts
|

Does Helicobacter pylori infection eradication modify peptic ulcer prevalence A 10 years' endoscopical survey

Abstract: Ten years of extensive Helicobacter pylori (H pylori) eradication in symptomatic patients led to a significant reduction in peptic ulcer prevalence. This reduction was particularly evident in Padova, where a project for the sensibilization of H pylori eradication among general practioners was carried out between 1990 and 1992. Should our hypothesis be true, H pylori eradication might in the future lead to peptic ulcer as a rare endoscopic finding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
19
3
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 7 publications
1
19
3
2
Order By: Relevance
“…Sökücü et al [43] reported a similar frequency of peptic ulcer but the prevalence of H. pylori positivity was found to be lower. Peptic ulcers located in the duodenum are usually related to H. pylori infection whereas gastric ulcers may be related to the use of NSAIDs and/or H. pylori infection [40][41][42]. The prevalence of peptic ulcer was 2.6% in this study, and it was astonishing to find a duodenal ulcer associated with H. pylori gastritis in such a group of young infants.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Sökücü et al [43] reported a similar frequency of peptic ulcer but the prevalence of H. pylori positivity was found to be lower. Peptic ulcers located in the duodenum are usually related to H. pylori infection whereas gastric ulcers may be related to the use of NSAIDs and/or H. pylori infection [40][41][42]. The prevalence of peptic ulcer was 2.6% in this study, and it was astonishing to find a duodenal ulcer associated with H. pylori gastritis in such a group of young infants.…”
Section: Discussionmentioning
confidence: 59%
“…The limited knowledge on this issue implies that peptic ulcers are not rare even during childhood and that the frequency shows a wide variation in different geographical areas, ranging from 5-35% [40][41][42]. The prevalence of peptic ulcer was 10.1% in children with a mean age of 11.5 years who underwent endoscopy in our center and the frequency of H. pylori infection was 86.1% in that group (unpublished data).…”
Section: Discussionmentioning
confidence: 88%
“…In addition, in the study by Gatta et al [4], a very similar prevalence of either duodenal (DU) or gastric ulcer (GU) is observed both in Italian (15.2 vs. 13.4%) and in immigrant (29.3 vs. 25%) patients. This would be in contrast with the higher prevalence of DU as compared to GU widely reported in literature (DU vs. GU = 3:1) [6]. As the Authors point out, the significance of all these findings remains unclear.…”
mentioning
confidence: 65%
“…Unexpectedly, peptic ulcer prevalence in this study would appear very high (29%), even in the Italian dyspeptic patients. Indeed, in previous studies performed in the same geographic area, peptic ulcer prevalence is cited as 6.3-17% [6,7]. Moreover, a prevalence rate as low as 2.7% on 11,148 consecutive upper endoscopy procedures is reported in a recent study performed in Rome [8].…”
mentioning
confidence: 94%
“…Some hypotheses could be put forward to explain the increased prevalence of the more virulent strains in dyspeptic patients and the low incidence of peptic ulcers in our geographic area. It is possible that H. pylori infection is largely cured in nonulcer dyspepsia patients due to its significant association with dyspeptic symptoms [25][26][27][28][29]. Indeed, a test-and-treat procedure is currently advised for dyspeptic patient management [30].…”
Section: Discussionmentioning
confidence: 98%